Risks of SARS‐CoV‐2 transmission between free‐ranging animals and captive mink in the Netherlands. Issue 6 (5th September 2022) - Sikkema, Reina S.; Begeman, Lineke; Janssen, René; Wolters, Wendy J.; Geurtsvankessel, Corine; de Bruin, Erwin; Hakze‐van der Honing, Renate W.; Eblé, Phaedra; van der Poel, Wim H. M.; van den Brand, Judith M. A.; Slaterus, Roy; La Haye, Maurice; et al.
Abstract: In the Netherlands, 69 of the 126 (55%) mink farms in total became infected with SARS‐CoV‐2 in 2020. Despite strict biosecurity measures and extensive epidemiological investigations, the main transmission route remained unclear. A better understanding of SARS‐CoV‐2 transmission between mink farms is of relevance for countries where mink farming is still common practice and can be used as a case study to improve future emerging disease preparedness. We assessed whether SARS‐CoV‐2 spilled over from mink to free‐ranging animals, and whether free‐ranging animals may have played a role in farm‐to‐farm transmission in the Netherlands. The study encompassed farm visits, farm questionnaires, expert workshops and SARS‐CoV‐2 RNA and antibody testing of samples from target animal species (bats, birds and free‐ranging carnivores). In this study, we show that the open housing system of mink allowed access to birds, bats and most free‐ranging carnivores, and that direct and indirect contact with mink was likely after entry, especially for free‐ranging carnivores and birds. This allowed SARS‐CoV‐2 exposure to animals entering the mink farm, and subsequent infection or mechanical carriage by the target animal species. Moreover, mink can escape farms in some cases, and two SARS‐CoV‐2‐positive mink were found outside farm premises. No other SARS‐CoV‐2‐RNA‐positive free‐ranging animals were detected, suggesting there was no abundant circulation in the species tested during the study period. To investigate previous SARS‐CoV‐2 infections, SARS‐CoV‐2 antibody detection using lung extracts of carcasses was set up and validated. One tested beech marten did have SARS‐CoV‐2 antibodies, but the closest SARS‐CoV‐2‐infected mink farm was outside of its home range, making infection at a mink farm unlikely. Knowing that virus exchange between different species and the formation of animal reservoirs affects SARS‐CoV‐2 evolution, continued vigilance and monitoring of mink farms and surrounding wildlife remains vital.